Health to health promotion : transforming health experience into nursing practice. - Caelli, Kathleen (Curtin University, 1998)
In contemporary Western nursing, the notion of health is considered a basic concept in all nursing theory, yet the many nursing theorists have failed to express unanimity in their various descriptions of health. This situation exists even while the achievement of health is generally identified as the goal or purpose of nursing. In Australia, the requirement that nurses become health-promoting practitioners assumes that nurses understand health in positive ways, which can be translated into nursing practice. Given the myriad definitions of health, confusion among nurses about the nature of health as it is to be promoted appeared possible, even probable.This phenomenological research aimed to illuminate the nature of nurses' understandings of health and the ways such understandings are translated into nursing practice. The purpose of the study was to describe and interpret nurses' experiences of health, and their experiences of giving health care to someone in their care, in order to illuminate the nature of health for nurses and in nursing.The manner in which this research was carried out was informed by the human science approach to phenomenology described by van Manen, which is derived from the traditions of Husserl, Heidegger and Merleau-Ponty. Thus, the inquiry was grounded in the hermeneutic phenomenological philosophical perspective, which began with the work of Husserl who recognised the need to return to the grounding of truths in human experience. The thesis is informed by two views of phenomenology. The first involves the traditional approach to phenomenology advocated by the European phenomenological philosophers while the second approach is referred to by Silverman as arising from 'American continental' philosophy.Data were generated from multiple audiotaped interviews with each of nine participants, and from personal reflection and journalling undertaken by the researcher during the research process. The dual data analyses were guided by the phenomenological approach of van Manen and by that of various nursing scholars who have used phenomenological methodology as it has evolved from American continental philosophy. These analyses included several levels of reflection undertaken by the researcher and each of the participants in the study to illustrate the nature of health in nurses' lives and in nursing.The nature of health, as revealed through the original experience of the participants, was disclosed as manifest in the lives of the participants with most descriptions conveying a sense of contentment that showed as feelings of happiness, feeling alive, complete, energised and optimistic. Health also revealed itself as transient in nature, passing quickly and without notice into and out of the lives of most of the participants. Although obvious in some ways, health simultaneously eluded clear description and, even at the completion of the exploration with each participant, was characterised by an atmosphere of elusiveness. For all the participants, health was an embodied phenomenon with a common element of energy and a sense of wellbeing. These, together with a sense that life was manageable and achievable gave to it a distinctive spirit, even while the spirit simultaneously helped to make life manageable and achievable and thus contributed to health. For all of those who participated, health presented as having the ability to transform their emotional responses to daily life events in such a way that it made those events more acceptable and the tasks of life more achievable.Although health showed as a physical, embodied state which was expressed as vitality and energy, it could not be separated from the mental / emotional state. As it was described, the following leitmotifs of health were lexically revealed: Health: A different encounter for each person, Health described as peace, Health described as feeling good about oneself, Health described as balance, Health as energy, Health as vitality and zest, Health described as happiness and/or contentment, Health described as quality of life, The 'picture of health', Health described as dignity, and Health as the unknown or the inexpressible.The nature of health-focused care in nursing showed as caring, rapport building and support, ever dependent on the social relationship that develops between each nurse-carer and the individual to whom they offer care. However, clear relationships between the meanings of health for the nurses in the study and the way they gave health care could not be elucidated. These relationships have not been identified because of the individualistic nature of health-focused care as these nurses have described it. For this reason, this research makes a strong plea for continued dialogue about the relationships between health and health-focused care in nursing.